Inscribing mining practice and theory: conceptions of knowledge production and the Iberian state in Capoche’s and Hinestrosa’s relaciones - Renée Raphael (Galilæana)
This contribution uses two narratives composed by practicing miners in Spain’s Viceroyalty of Peru to explore period conceptions of the Iberian state’s interest in metallurgical knowledge. Luis Capoche’s 1585 Relación general … de Potosí (“General Relation of Potosí”) and Juan Francisco de Hinestrosa’s 1596 Relación breve y sumaria … del descubrimiento … de nuebo Potosí (“Short relation and summary of the discovery of New Potosí”) evince parallels in content and form. While these similarities can be attributed merely to the context of colonial Iberian mining administration, they also point to a horizon of expectations shared by these authors and their intended readers, the viceroy and king. An exploration of the varied ways that Capoche and Hinestrosa marshalled theoretical and practical metallurgical knowledge in their writings enriches previous scholarship that has argued for the Iberian state’s interest in and promotion of knowledge production.